(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Assessing the treatment outcomes of vinorelbine in patients with recurrent or metastatic non-small cell lung cancer (NSCLC) in Thanh Hoa Oncology Hospital. Patients and Methods: Descriptive, longitudinal study in 135 patients with recurrent or metastatic NSCLC who received vinorelbine in Thanh Hoa Oncology Hospital from June 2021 to September 2024. Results: The study was carried out on 135 patients. Median age was 66,7 ± 8,2; the male/female ratio was 1,9/1. The most common presenting symptoms were cough, chest pain, dyspnea were 81,5%, 68,9%, 60%, respectively. The most frequent sites of recurrence were local, pleural and supraclavicular lymph nodes, and most patients had lesions in two or more sites (68,1%). The mean number of vinorelbine cycles administered was 6,8 ± 3,2, with most patients receiving ≥ 85% of the planned dose. The disease control rate was 65,2%. There was no significant difference in response rate according to age, sex, histological subtype or number of metastatic sites. The mean progression-free survival (PFS) was 7,1±12,4 months, with a median of 4,6 months. Conclusion: Vinorelbine monotherapy for patients with recurrent or metastatic NSCLC achieved a high disease control rate and prolonged progression-free survival.